TWO-COMPONENT VARIABILITY OF THE SEMI-REGULAR PULSATING STAR U DELPHINI - Andronov, I. L.; Chinarova, L. L. (Одеські астрономічні публікації, 2012)
Photometric analysis of photometric variability of the semi-regular pulsating variable U Del is analyzed. From the international AFOEV database, 6231 brightness values in the time interval JD 2451602-55378 were chosen. For the periodogram analysis, we have used a trigonometric polynomial fit. Using the criterion of minimal variance of the approximation at arguments of observations, the optimal degree is s=1. Initial epoch for maximum is T0=JD2453340±3, the period P=1198±4d. Mean brightness at maximum is 6.624±0.005, at minimum 7.124±0.005, i.e. the amplitude is 0.499±0.005m. Besides this slow variability, there is a faster oscillation of a period of 119.45±0.06d, amplitude 0.303+0.005m and an initial epoch for maximum 2453215.1±0.5. These results are mean during the time interval after that analyzed in the catalogue of Chinarova and Andronov (2000). Also the method of "running sines" with a filter half-width Δt=0.5P. The local mean (averaged over a short period) brightness varies in a range 6.58-7.41m , the semiamplitude exhibits very strong variations from 0.01 to 0.46m . The phase is also variable - typically of a full amplitude of 0.5. Close to JD 2452589, occurred a phase jump by a complete period during a descending branch of a slow wave. This effect was not observed during other cycles. No significant correlation between mean brightness and amplitude of short-period oscillation was found. Despite significant variability of amplitude, the periodic contribution is not statistically significant. Also characteristics of individual brightness extrema were found. The study was made in a course of the international project "Inter-Longitude Astronomy" (Andronov et al., 2010) and national project "Ukrainian Virtual Observatory (Vavilova et al., 2012).